Pair Trawling vs. Otter Trawling: An evaluation of efficiency along the Southwest Coast of India - Madhu, V. R.; Sasikumar, Geetha; Viswambharan, Divya; Rohit, Prathibha; Chaniappa, M.; Rajesh, K. M.; Sayana, K. A.; Pravin, P. (Fishery Technology, 2021)
In Karnataka, the trawling industry contributes significantly to fish landings. Though conventional otter trawlers account for the majority of trawl landings in the state, pair/bull trawling, which is prohibited, also during the post-monsoon season. There are no published reports on the specifications of the gear used or the changes operation, in the region over the last few years. A comparison of pair/ bull trawls and mid-water finfish otter trawls operating off the coast of Karnataka was conducted. The specifications for the gears were gathered from the gear fabrication units in Mangalore and Malpe. The pair trawlâ€™s head rope (HR) measured 183â€“293 m in length, while the finfish otter trawlâ€™s HR measured 99â€“110 m. The pair trawls had a mouth opening that was between 2.9â€“4.06 times that of the mid-water finfish otter trawls. Trawlers operating along the Karnataka coast conducted both pair and otter trawling during the same cruise, depending on the circumstances. The study indicates that the catch rate was significantly higher in pair trawls than in otter trawls. The average drag produced by pair trawls was calculated to be 6.74 tonnes at a speed of 3.0 kn, while the drag produced by otter trawls was only 2.28 tonnes at the same speed. The result of the study indicates that while the high fuel consumption of a pair trawling unit may negate some of the profits, the overall profit margin of the unit remains high during pair trawling, enticing fishermen to engage in clandestine pair trawling.Capping engine power, regulating gear size and operation and enforcing legal mesh sizes through stringent â€œmonitoring, control and surveillanceâ€ mechanisms mitigate the negative impacts of pair trawling.